Research on beam quality control technology of 2 μm antimonide semiconductor laser - Li, Sensen; Zhang, Jingsheng; Cheng, Xiangzheng; Shao, Ming; Liu, Qianghu; An, Jiashuo; Li, Shun; Fan, Xinmin (Frontiers in Physics, 2022)
Antimonide semiconductor laser is a new type of laser with unique advantages in the 2 μm band. However, employing FP cavities causes multiple transverse modes to degrade beam quality despite achieving higher power output. In this paper, an antimonide semiconductor laser operating in 2 μm band is realized by utilizing fiber direct coupling and multiplexing. Fiber multiplexing results in higher output power, while uniform patterns in both near-field and far-field are obtained, and beam quality is improved. The experimental results illustrate that the laser output in the 2 μm band reaches 1.2 W after 7-channel beam combination, and the near-field distribution is approximately Gaussian, while the far-field exhibits a flat-top distribution.